ANALISIS PENGARUH KEPEMILIKAN SAHAM PUBLIK, PROFITABILITAS, MANAJEMEN HUTANG DAN LIKUIDITAS TERHADAP PENGUNGKAPAN TANGGUNGJAWAB SOSIAL PERUSAHAAN PADA LAPORAN TAHUNAN PERUSAHAAN YANG BERGABUNG DILQ45 SUB SEKTOR PROPERTY AND REAL ESTATE TAHUN 2012-2016 - AGUSTIANI, NURUL; BRAHMAYANTI, IDA AYU SRI (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2019)
ABSTRACTSocial and environmental responsibility is a commitment of the Company to participate in sustainable economic development in order to improve the quality of life and a useful environment. The Company shall also take into accountthe interests of management, owners, employees, consumers and the public. The purpose of this study isto examine the analysis of the effect of public stock ownership, Profitability, Debt Management and liquidity on corporate social responsibility disclosure on the annual report of companies that joined in LQ45 sub-sector Property and Eeal Estate year 2012-2016. Thepopulation in this study covers all companies that join the Index LQ45 listed on the Indonesia Stock Exchangees. Total sampple of research is as many as 5company sample sub-sector Property and Real Estate by using purposive sampling method. Data analysis techniques using multiple linear regression analysis, while the hypothesis test used is the coefficient of determination multiple (R2), F test, t test, and coefficient of determination (R2).The results of the study show that: (1) Public share ownership does not significantly influence corporate social responsibility, (2) Profitability significantly influence corporate social responsibility disclosure, (3) Debt management significantly influence corporate social responsibility(4) Liquidity does not significantly influence corporate social responsibility disclosure, (5) Public share ownership, profitability, debt management, liquidity do not significantly affect corporate social responsibility disclosure. Based on the results ofÂ researchthat has been done then proposed suggestion is the addition of new variables, Samples, and Period of research. The addition of new variables is useful for determining other factors that will determine the disclosure of corporate social responsibility. The addition of the sample and the study period can improve the results of the research so that it can be generalized better.Â Keywords: Public stock ownership, Profitability, Debt management, liquidity and corporate social responsibility